Korporacyjne regulacje pozaprawne a systemowość prawa. Zarys problemów - Jabłońska-Bonca, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The purpose of the paper is to draw attention to the impact of the modern corporate normative environment in specific legal systems on the systemic nature of law.The subjects of analysis are the autonomous adjustments made by large, global economic corporations that create global practices, standards and principles of operation for certain categories of recipients. Practices, standards, guidelines, regulations, etc. are forms of self-regulation.The author presents three types of regulatory responses of global corporations to law, distinguishing them based on the main object and the specificity of the impact area.Different types of corporations calculate differently the regulatory, financial and reputational risks — therefore react differently to laws. Reaction mechanisms are described in this paper.
Keywords: korporacje globalne; natura prawa; systemowość prawa; regulacje pozaprawne